Two cases of isolated first rib fracture. Issue 6 (1st November 2001) - Vikramaditya,; Pritty, P
Abstract : Isolated first rib fractures are uncommon. They are usually associated with severe blunt trauma, although other mechanisms have been suggested, these being (a) indirect trauma, (b) sudden contraction of the neck muscles, and (c) stress or fatigue fractures attributable to repeated pull of muscles. Two cases are reported of stress fracture of the first rib, who presented to the accident and emergency department.